Positive Academic Leadership - Jeff Buller (Academic Chairpersons Conference Proceedings, 2018)
A highly interactive session that explores strategies for achieving positive outcomes in event he most negative situations, changing your focus from putting out fires to making a real difference, and promoting a more constructive work environment.
Keywords: Positive Academic Leadership Interactive Strategies